The Effect of Discipline and Training Toward Employee Performance - Melda Wiguna (Almana : Jurnal Manajemen dan Bisnis, 2020)
Organizational resources that have an important role in achieving its goals is human resources. Because of the importance of the role of humans in both short and long term competition on the business agenda, a company must have more value compared to other companies. PT. Mediatama Sejahtera is a company engaged in comprehensive services consisting of printing services (transactional printing service), electronic report making services (E-statement service), printing services (publishing printing service), document scanning services (document imaging service/scanner), Courier service, as well as customized business process management services, business process management services. This study aims to determine the effect of discipline and training on employee performance at PT. Mediatama Sejahtera in Jakarta. The method used was explanatory research with a sample of 86 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study have a significant effect on discipline employee performance by 46.3%, the hypothesis test obtained significance 0,000 <0.05. The training had a significant effect on employee performance by 35.9%, the hypothesis test obtained a significance of 0,000 <0.05. Discipline and training simultaneously have a significant effect on employee performance. hypothesis-testing obtained significance of 0,000 <0.05